Analisis Perbandingan Debit Air pada Sistem Damkar Viar Menggunakan Bahan Bakar Pertalite dan LPG - Nursyawal, Wira Agung; Rasid, Muhammad; Hidayati, Baiti (Politeknik Negeri Lhokseumawe, 2025)
Small-sized fire fighting vehicles such as the three-wheeled Viar are a practical solution for reaching narrow and dense locations. This study aims to compare the water pump engine based on the discharge generated when using two types of fuel, namely Pertalite and LPG gas, in the design of the three-wheeled Viar Fire Fighting System. The main focus of the research is on how much water discharge can be generated and how the operational cost efficiency of each fuel. The method used is direct experimentation, where the pump is run at a fixed engine speed of 2400 RPM. The volume of water pumped is measured at a certain duration to obtain the discharge value. In addition, the fuel consumption was analyzed and the cost incurred in one pump cycle was calculated. In order for the LPG test to run optimally, the carburetor was modified to adjust the characteristics of the gas fuel.